تشتت الانتباه المصحوب بفرط الحركة لدى ذوي عسر القراءة - بيه, جهاد; واكواك, صبرين (جامعة الوادي university of Eloued, 2022)
الملخص: تهدف الدراسة الى التعرف على تشتت الانتباه المصحوب بفرط الحركة لدى تلاميذ السنة الخامسة ابتدائي معسري القراءة, وتمحورت اشكالية الدراسة في التساؤل التالي : ما مستوى تشتت الانتباه المصحوب بفرط الحركة لدى تلاميذ عسر القراءة وذلك بالاعتماد على منهج دراسة الحالة عن طريق أدوات الملاحظة وتطبيق "اختبار رافن للمصفوفات المتتابعة الملون" و"اختبار لعيس للقراءة" وكذلك "مقياس كونرز لتقدير سلوك الطفل" على العينة المختارة بأسلوب غير عشوائي وبطريقة قصدية وتتكون من ثلاث حالات تلميذين وتلميذة يتمدرسون بالصف الخامسة ابتدائي. وبعد المعالجة الاحصائية لمعطيات المستمدة من الميدان تم التوصل الى النتائج التالية : يوجد لدى تلميذ السنة الخامسة ابتدائي ذو عسر القراءة تشتت انتباه مرتفع وفرط حركة متوسط. يوجد لدى تلميذان السنة الخامسة ابتدائي ذو عسر القراءة تشتت انتباه مرتفع وكذلك لديهم فرط حركة مرتفع. Abstract: The study aims to identify the attention-distraction accompanied by hyperactivity among fifth-year dyslexic students, the problem of the study centered on the following question: What is the level of attention deficit hyperactivity disorder among dyslexic students? The case study method was used based on observation and the application of the "Raven's Test of Colored Progressive Matrices" and "layes Test for Reading" as well as the "Conners Scale for Estimating Child Behavior" on the selected sample in a non-random and intentional manner. it consists of three cases of two male and female students studying in the fifth grade of primary school. After statistical treatment of data from the field, the following results were obtained: One fifth year primary student with dyslexia has high inattention and moderate hyperactivity. Two fifth year primary students with dyslexia have high inattentiveness as well as high hyperactivity.
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: تشتت الانتباه، عسر القراءة; Trouble déficitaire de l'attention, dyslexie; Attention deficit disorder, dyslexia